Effect of Ultrasound on Enzymatic Extraction of Zingiber Officinale - Fatinnurhazwani, Zainal (2013)
The production of essential oils from natural sources is highly profitable nowadays. The herbaceous perennial of ginger has been used as spices and is common condiment in variety of foods and beverages. Ginger is scientifically known as Zingiber officinale. This study is focused to extract the essential oil of ginger by using the technique of enzymatic extraction assisted with ultrasound in order to maximize the percentage of oil yield. Enzymatic extraction since past few decades had been acclaimed as the alternative process to produce the essential oil of herbs and oilseeds which more economically and environmental friendly than usual conventional extraction. This research has been carried out by using enzyme pectinase with different concentration from 1%, 1.5%, 2% and 3% for enzymatic extraction. The ultrasound procedure was performed by 10% and 20% duty cycle. As result indicates that by using enzymatic extraction method assisted with ultrasound, the high and good quality production of ginger oil was obtained. Pectinase concentration of 2% (v/w) yielded the highest percentage of oil recovered which is 66% and with 10% duty cycle of ultrasound, the yield was increased to 73.7% compared to solvent extraction yielded about 39% oil. As a conclusion, apart from being effective and as an alternative to conventional method, enzymatic extraction assisted with ultrasound also discovers the potential reduction of solvent consumption.